Anthropometric Changes Using a Walking Intervention in African American Breast Cancer Survivors: A Pilot Study - James Kilpatrick, PhD; Gwen Parker, MS; Diane B. Wilson, EdD, MS, RD; Jerlym S. Porter, MS (Centers for Disease Control and Prevention, 2005)
Introduction African American women exhibit a higher mortality rate from breast cancer than do white women. African American women are more likely to gain weight at diagnosis, which may increase their risk of cancer recurrence and comorbidities. Physical activity has been shown to decrease body mass index and improve quality of life in cancer survivors. This study was designed to evaluate the feasibility and impact of a community-based exercise intervention in African American breast cancer survivors. Methods A theory-based eight-week community intervention using pedometers with scheduling, goal setting, and self-assessment was tested in a convenience sample of African American breast cancer survivors (n = 24). Data were collected at three time points to examine changes in steps walked per day, body mass index, and other anthropometric measures, attitudes, and demographic variables. Results Statistically significant increases in steps walked per day and attitude toward exercise as well as significant decreases in body mass index, body weight, percentage of body fat, and waist, hip, and forearm circumferences, as well as blood pressure, were reported from baseline to immediate post-intervention. Positive changes were retained or improved further at three-month follow-up except for attitude toward exercise. Participant retention rate during eight-week intervention was 92%. Conclusion Increasing walking for exercise, without making other changes, can improve body mass index, anthropometric measures, and attitudes, which are associated with improved quality of life and reduced risk of cancer recurrence. The high participant retention rate, along with significant study outcomes, demonstrate that among this sample of African American breast cancer survivors, participants were motivated to improve their exercise habits.